Electromechanical devices & components illustrated sourcebook - Elliott, Brian S. (McGraw-Hill's AccessEngineering., 2007)
"Ideal for anyone who designs, repairs, and operates electromechanical equipment, Electromechanical Devices & Components Illustrated Sourcebook provides 2,000 illustrations of the most commonly used elements found in today's electromechanical machines and systems. This essential working tool contains detailed diagrams, drawn to scale, with relevant calculations and tabular information presented for easy reference."--Jacket.